PERSPECTIVAS HISTÓRICAS E POLÍTICAS DA PARTICIPAÇÃO DA ENFERMAGEM NO MERCOSUL. - Cássia Cristina Freitas Leite; Elioenai Dornelles Alves (Universidade Federal de Goias, 1999)
It is a reflection on the historical and political aspects that influenced and are present in the practice and formation of the nursing professionals and of health in the attempt of contributing as a standard for the development of knowledge in the area of the health and of projects of national and international cooperation with views the promotion of the quality transcultural of life of the Latin-American population. Its stands out in the text the inclusion of the historical aspects and the walks of the nursing in the last decade heading for an effective participation in the world project of globalization. Some points of view are presented as subjects that need to be deepened by the professionals of the health and, specifically of the nursing for the continuity in other approach on the theme.